2021
DOI: 10.1088/1674-1056/abfcca
|View full text |Cite
|
Sign up to set email alerts
|

Helium-hydrogen synergistic effects on swelling in in-situ multiple-ion beams irradiated steels*

Abstract: The development of reliable fusion energy is one of the most important challenges in this century. The accelerated degradation of structural materials in fusion reactors caused by neutron irradiation would cause severe problems. Due to the lack of suitable fusion neutron testing facilities, we have to rely on ion irradiation experiments to test candidate materials in fusion reactors. Moreover, fusion neutron irradiation effects are accompanied by the simultaneous transmutation production of helium and hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The increase of swelling caused by He-H synergistic effects in materials under different experimental conditions had been demonstrated in previous studies (Farrell and Lee, 1985;Farrell and Lee, 1987;Sekimura et al, 2000;Tanaka et al, 2004;Borodin et al, 2013;Brimbal et al, 2015;Kupriiyanova et al, 2016;Liu et al, 2021). However, some results (Farrell et al, 1978;Hamada et al, 1997;Kupriiyanova et al, 2016;Jiang et al, 2020) showed that He-H synergistic effects on swelling are not monotonic, indicating that the swelling may not always be enhanced but also be suppressed under triple beam irradiation.…”
Section: He-h Synergistic Effects On Cavity Evolution and Swellingmentioning
confidence: 69%
See 2 more Smart Citations
“…The increase of swelling caused by He-H synergistic effects in materials under different experimental conditions had been demonstrated in previous studies (Farrell and Lee, 1985;Farrell and Lee, 1987;Sekimura et al, 2000;Tanaka et al, 2004;Borodin et al, 2013;Brimbal et al, 2015;Kupriiyanova et al, 2016;Liu et al, 2021). However, some results (Farrell et al, 1978;Hamada et al, 1997;Kupriiyanova et al, 2016;Jiang et al, 2020) showed that He-H synergistic effects on swelling are not monotonic, indicating that the swelling may not always be enhanced but also be suppressed under triple beam irradiation.…”
Section: He-h Synergistic Effects On Cavity Evolution and Swellingmentioning
confidence: 69%
“…In the column of "the effect of He" in Table 1, the presence of He in dual-beam irradiation increases the density and decreases the size of cavities in almost all cases. Besides, in some studies (Brimbal et al, 2015;Liu et al, 2021), researchers observed no cavities in materials under single HI irradiation, while cavities emerged under dual beam (HI + He) irradiation. This indicates the role of He in prompting cavity nucleation.…”
Section: The Role Of He and H In Synergistic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, a number of studies [174][175][176][177][178][179][180][181][182][183][184][185][186][187][188][189][190] have been carried out within the framework of synergistic effects between radiation damage and transmutation gas production, but their results are not always consistent. The increase in swelling due to He-H synergistic effects had been demonstrated in the earliest investigations conducted by Farrell and Lee [174] using dual beam (Fe + He) and triple beam (Fe + He + D) irradiation of Fe10.5Cr6Mo ferritic/martensitic steel to 100 dpa and a gas co-implantation level of 40 appm D/dpa and 10 appm He/dpa at 500 °C.…”
Section: He and H Synergistic Effects On Radiation Hardening And Swel...mentioning
confidence: 99%
“…MSIB irradiation has been used for many years to study the He-H synergistic effects on cavity behavior and the swelling of materials. Many results have shown that swelling was significantly enhanced, even up to a hundred times [15,16]. These results raised concerns about the performance of materials in the fusion reactor environment, however, they were also questioned due to the high damage rates of MSIB experiments.…”
Section: Introductionmentioning
confidence: 99%